Analisis Pengawas Intern, Gaya Kepemimpinan dan Persepsi Bawahan terhadap Perilaku Atasan untuk Meningkatkan Kinerja Manajerial pada PT Telkom Gresik - Soegiono, Pandyi (Jurnal Aplikasi Manajemen, 2009)
Company which was activity of is effort excelsior, hence will progressively problems complex having the character of managerial and at condition that way leader need effort which have been specified in reaching effort target which have been specified. Problems faced by company is the existence of very tight emulation storey; level to performance of managerial between divre-divre at PT. Telkom Gresik. This research is executed by survey by using primary data of responder becoming research object. Hypothesis the raised is set of internal control by simultaneous have an effect on to performance of managerial, but by partial set of internal control do not have an effect on. While leadership style (leadership) and also perception of subordinate to behavior of superior, by partial and simultaneous have an effect on to performance of managerial. Data-processing by using statistical test of double linear regression. Analysis result can be concluded that there are relation by simultaneous between set of observation, leadership style and also perception of subordinate to behavior of superior have influence to performance of managerial. Dominant influence to performance of managerial at PT. Telkom Gresik in gresik is perception of subordinate to behavior of superior.